2012
DOI: 10.1080/00380768.2012.715070
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thai rice cultivars with low-grain cadmium

Abstract: To identify rice cultivars with low grain cadmium (Cd) levels, 42 cultivars of Thai rice (Oryza sativa L.) were cultivated in a Cd-contaminated field in the Pha Te village, Mae Sot district, Tak province, Thailand, from 2009 to 2011. Among non-glutinous and late-ripening cultivars, lower levels of Cd accumulated in the grains of RD5, RD15, and Sang Yod than in Khao Dawk Mali 105, a prevailing and popular cultivar in this area. Among glutinous and late-ripening cultivars, Khao' Niaw Ubon 1 and Khao' Niaw Ubon 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…It is thus regarded as a serious global problem with an impact on stability of ecosystems and on safety of food sources. Safe food sources with reduced cadmium content have been sought to decrease exposure by cadmium [44].…”
Section: Discussionmentioning
confidence: 99%
“…It is thus regarded as a serious global problem with an impact on stability of ecosystems and on safety of food sources. Safe food sources with reduced cadmium content have been sought to decrease exposure by cadmium [44].…”
Section: Discussionmentioning
confidence: 99%
“…Sriprachote et al [22] had revealed that growing on the same contaminated paddy fields in Mae Sot District, specific Thai-rice cultivars RD5 (0.108 mg kg -1 ), RD15, KNU1 (0.125 mg kg -1 ) and KNU2 (0.179 mg kg -1 ) had significantly lower Cd concentrations in their grain than the prevailing cultivars KDML105 and RD6 (0.740 mg kg -1 ). The current survey for 6-years monitoring which the authors had encouraged the farmer to grow the promising low grain-Cd rice cultivar RD15 instead of the prevailing cultivar KDML105, since 2012, in harmony with the previous research [22], under the same conditions, the RD15 had lower Cd concentration than the one determined from the KDML105. Comparison between both cultivars, the RD15 had 80% of Cd lower than the KDML105.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variations in Cd accumulations in rice grains are reported [18][19][20][21]. Sriprachote et al [22] have studied varietal difference in Cd uptake among prevailing Indica rice cultivars in the contaminated paddy fields of the Pha Te Village of Mae Sot District, and concluded that RD15 cultivar had lowest Cd concentration in grain (0.197 mg kg -1 ) compared with the prevailing cultivar KDML105 (0.58 mg kg -1 ), and lower than the maximum concentration of 0.4 mg kg -1 polished rice. The results indicated that by selecting rice genotype with low-grain Cd cultivars, human Cd intake from rice consumption and the resulting health risk could be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of planting pollution-safe cultivars or low Cd-accumulating varieties in contaminated areas to accumulate the pollutant in their grains at a sufficiently low level for safe consumption has been previously proposed (Yu et al 2006;Sriprachote et al 2012a;2012b). Based on the lower Cd content in the grain, these authors suggested that alternative varieties of rice should be grown in Cd-contaminated areas.…”
Section: Discussionmentioning
confidence: 99%